Republic of Madagascar : Poverty Reduction Strategy Paper Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper examines the first annual report on the implementation of Madagascar's Poverty Reduction Strategy Paper (PRSP). The report reviews the status of achievements on policy measures, action plans, as well as reforms concerning the Initiative for the Heavily Indebted Poor Countries (HIPC). It covers the first year of PRSP implementation corresponding to the period from July 2003 to June 2004. It also highlights the connections between the achievements and objectives, programs, and indicators.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet